A new species of Andinia subgen. Brachycladium (Orchidaceae: Pleurothallidinae) from Colombia - Vieira-Uribe, Sebastián; Karremans, Adam P. (Lankesteriana: International Journal on Orchidology, 2017)
A new species of Andinia belonging to A. subgenus Brachycladium from the eastern Andes of southern Colombia is described and illustrated. Andinia obesa is related to the A. nummularia species complex, characterized by the glabrous leaves, short inflorescences, an inconspicuous trilobed lip and a relatively large column. The new species can be distinguished by the unusually plump, orbicular, cucullate column with an incumbent anther.